ANALYSIS OF MAXILLARY FRACTURE PATIENTS PROFILE IN A TERTIARY GENERAL HOSPITAL (2018-2020) - Suarta, I Dewa Gde Daniswara; Agus Santoso Budi; Rosy Setiawati; Magda Rosalina Hutagalung (Universitas Airlangga, 2023)
Highlights: Maxillary fractures predominantly affected adult males aged between 18 and 64, comprising 92.36% of the cases studied. The most common type of maxillary fracture observed was Le Fort 3, followed by other Le Fort classes. The preferred treatment method for maxillary fractures was ORIF mini plating, which resulted in favorable outcomes with minimal complications. Abstract: Introduction: The maxilla is a crucial bone in the midface, playing a significant role both functionally and cosmetically. Analyzing the medical records of maxillary fractures at Dr. Soetomo General Academic Hospital would offer an overview of the various treatments used and their corresponding outcomes were the aim of this study. This data would provide a general understanding of the patient's conditions during maxillary fracture treatment and could potentially support further research in this field. Methods: In this study, data on the profile, treatment, and management of maxillary fractures were taken from patient medical records at Dr. Soetomo General Academic Hospital between 2018 and 2020. Result: The study examined 144 cases of maxillary fractures at Dr. Soetomo General Academic Hospital, analyzing medical records and surgery reports from 2018 to 2020. Most of the patients (92.36%) were adult males (78.47%) aged between 18 and 64. The most common type of maxillary fracture observed was Le Fort 3 (47.22%), while other Le Fort classes accounted for fewer cases. The preferred treatment method was ORIF mini plating (81.25%), and the average hospital stay was around 12.56 days. Only one patient experienced post-treatment malocclusion in the 144 cases. In terms of complications, there were minimal instances of infections and exposed plates, with a total of four cases reported. Conclusion: The treatment outcomes at Dr. Soetomo General Academic Hospital showed lower incidence rates of post-surgical issues like malocclusion, infections, and exposed plates when compared to other current datasets.